Response of the zoobenthos community along the dispersion plume of a highly polluted stream in the receiving waters of a large river (Rio de la Plata, Argentina) - Paggi, Analía C; Ocón, Carolina; Tangorra, Mariana; Capítulo, Alberto Rodrigues (Hydrobiologia, 2006)
The ingress of an urban stream carrying high contaminant loads into a large coastal river originates a “dispersion plume” subject to the hydrological conditions of a river affected by tidal influences. In the present study 21 sites within the “contaminant plume” of the Riachuelo River in the Rio de la Plata were analysed on the same date in order to evaluate the biological status of the area which receives this strong environmental impact, and to examine its effect on the zoobenthic communities. Diversity, taxonomic richness, abundance, physico-chemical parameters and a biological index (IMRP) were used to assess the responses of the macroinvertebrates. The correlation between exposure and effect was calculated by means of the exposure index (IEX). The relationship between the macroinvertebrate communities and environmental variables was examined using CCA analysis. Conductivity, Cr, BOD and COD, were most strongly correlated with Axis 1, suggesting the existence of a gradient of environmental degradation. The most severely contaminated sites (IMRP= 1.1–2.5; IEX = 100–78%) were all characterized by a reduced community dominated by Nematoda and Oligochaeta. A moderate response was observed between 1400 and 1600 m from the coast (IMRP = 2.6–3.9; IEX = 36%) largely owing to the physico-chemical characteristics of the recipient river which contributed to moderating the effect of the anthopogenic perturbation. For statistical validation, this area was compared with historical physico-chemical and biological data, where OD and COD showed the same tendency throughout the 10-year period.